Modelling Governance Indicators and Managing e-Business Information Systems - Nimmagadda, Shastri; Mani, Neel; Reiners, Torsten; Wood, Lincoln (2020)
Information Systems are in growing demand in various business and government organizations. Despite increased competition, business growth and technology innovation, at times, we overlook the governance, transparency, integrity and business ethics, with the result, the quality of deliverable products and services is compromised. Several external factors such as corruption, ineffective governance, political instability, flawed regulations and violation of rules of law, unaccountability affect the connectivity between outside influences and technology implementations. To summarize, weak governance practices and unjustified business ethics are impediments to business IS implementations. Appropriate technological innovations and remedial measures are needed that can substantiate our adaptation and implementation measures. The challenges are examined in the form of a three-tiered technology development motivation, which consists of mitigation, adaptation and implementation actions. We explore the relevant issues and challenges, and the need for a holistic IS research approach with follow-up technological remedies and accountability of results in the affected geographies and demography. The purpose of the research is to build IS artefacts to link governance attributes with the lapses existing between information management, organization strategies and e-business needs. An integrated IS architecture is proposed to explore the congruence between governance indicators and e-business IS requirements. The study further explores the wide-ranging of governance indicators that affected the business IS development and implementation. Cognizance of governance facts and their modelling in e-business contexts are pathways to instigate business IS artefacts and manage their needs in industry scenarios. Based on empirical research done on attribute modelling for 200 governments worldwide, we articulate our research findings with a claim that the e-business objectives are accomplishable through successful implementation of IS architectures in industrial environments through improved governance and transparency. Various IS strategies emerge to rescue the business and organization openness and transparency. Mitigation and critical interrogation of governance indicators facilitate us understand the research phenomena and adaptation of IS artefacts that accustomed to e-business change management. Models describing affected governments, documentation in the form of multidimensional repositories, with sustainability-manifested management and accounting are the outcomes of the research. Implementation of articulated IS architecture, and its adaptations by business and government organizations ensure us smart and sustainable e-business solutions in place, operationalizing governance policies, as adhered by various stakeholders. The research offers sustainable IS artefacts and online services to multiple government organizations and businesses. The benefits of the research are multifold, and they are improved internal operations and delivery of quality public services through established electronic services. Reduced waiting times, raising transparency, reinforcing equalities, and smoothening of the overall functioning of the organizations are added benefits of the study. Cost savings, improved communications, and increased government accountability are other gains of the study